Representaciones sobre el cáncer y la muerte en adultos jóvenes diagnosticados con leucemia - Cárdenas Fajardo, Nicole Andrea (2023)
The objective of the present study was to know the responses regarding the representations of the experience of cancer and death in a group of young adults diagnosed with leukemia. For this purpose, an in-depth interview was carried out with 12 patients between the ages of 18 and 28, who presented said diagnosis. The interest directed towards this particular group was based on the fact that, at this stage, people go through psychological, family, academic and work changes, so they wanted to investigate how they perceived the disease, as well as what the stages were. that predominate. That being said, different feelings towards death were evident, such as fear, sadness, frustration and guilt. Likewise, a lot of concern regarding the diagnosis, associated with the academic or work future and economic issues. In the same way, different meanings were evidenced towards leukemia as an incurable and long-term disease and also different stages of mourning such as avoidance, anger, and depression.